Robotic Magnetorheological Finishing Technology Based on Constant Polishing Force Control - Lin Zhang; Chunlei Zhang; Wei Fan (Applied Sciences, 2022)
The normal positioning error hinders the use of magnetorheological finishing (MRF) in robotic polishing. In this paper, the influence of robotic normal positioning error on the MRF removal rate is revealed, and a force-controlled end-effector for the robotic MRF process is presented. The developed end-effector is integrated into a six-axis industrial robot, and the robot positions the end-effector while the end-effector realizes the constant force control. A fused silicon mirror is polished, and the result shows that the proposed device effectively compensates for robotic normal positioning error and simultaneously maintains the stability of the polishing process. After deterministic polishing, the PV (peak to valley) of the figure is reduced from <semantics>126.56nm</semantics> to <semantics>56.95nm</semantics>, and the RMS (root mean square) is reduced from <semantics>22.15 nm</semantics> to <semantics>7.59 nm</semantics>.